Intraocular pressure effect of intravitreal conbercept injection for retinopathy of prematurity - Gao, Caifeng; Mu, Ge; Zhao, Huanhuan; Zheng, Jiao; Feng, Qingyang; Wu, Yining; Li, Yinan; Huang, Xuelin; Sun, Wei (Frontiers in Pharmacology, 2023)
Purpose: Intravitreal injection of conbercept (IVC) is a novel anti-vascular endothelial growth factor (anti-VEGF) treatment for retinopathy of prematurity (ROP). This study aimed to assess the intraocular pressure (IOP) effect of IVC. Methods: All IVC surgeries were performed in the Department of Ophthalmology, Guangdong Women and Children Hospital, from January 2021 to May 2021. In this study, 30 eyes of 15 infants who received intravitreal injections of conbercept at a dose of 0.25 mg/0.025 mL were included. TheIOP of all participants was measured prior to administering the injection and subsequently at 2 min, 1 hour, 1 day, and 1 week thereafter. Results: We included 30 eyes (10 boys and 5 girls) with ROP. For the male group, the mean birth weight, mean gestational age at birth, and the mean time of postmenstrual age (PMA) at IVC treatment were 1174.0 ±446.0 g, 28.4 ±3.0 weeks, and 37.1 ±1.6 weeks, respectively; for the female group, they were 1108 ±285.5 g, 28.2 ±2.5 weeks, and 36.8 ±2.1 weeks, respectively. For the male group, the IOP at baseline, 2 min, 1 hour, 1 day, and 1 week after IVC were 12.4 ±1.5 mmHg, 49.0 ±3.1 mmHg, 26.3 ±2.5 mmHg, 13.4 ±2.2 mmHg, and 11.6 ±1.7 mmHg, respectively; for the female group, they were 10.7 ±2.0 mmHg, 47.3 ±3.2 mmHg, 26.4 ±3.2 mmHg, 10.7 ±1.8 mmHg, and 10.2 ±1.8 mmHg, respectively. In both groups, the IOP immediately (2 min) after the operation was significantly higher than that at any other time point (P<0.01). IOP values returned to the preoperative baseline level on the first day after surgery, with no significant difference compared with that before injection (P>0.05). IOP continued to be maintained at the preoperative baseline level on the first week after surgery, with no significant difference compared with that before surgery (P>0.05). Conclusion: Infants with ROP who received IVC experienced a sharp increase in the IOP immediately after injection, which decreased to below 30 mmHg after 1 hour and maintain that level for 1 week or longer.